Moisture uptake during washing and spray chilling of Holstein and beef-type steer carcasses - Johnson, R.D.; Hunt, Melvin C.; Allen, Dell M.; Kastner, Curtis L.; Danler, R.J.; Schrock, C.C. (American Society of Animal Science, 2008)
This study was conducted at a commercial beef slaughter plant to determine the effects of carcass washing, intermittent spray chilling and carcass fatness on carcass weight yields and on moisture content of cutaneous trunci muscle and s.c. adipose tissue (AT) samples excised from two carcass locations. Beef steer carcasses (n = 36) initially had 12.8% moisture in AT. Immediately following washing, AT from the sirloin region had more (P < .01) moisture (24.5%) than AT from the fifth-rib region (15.6%). Fat (n = 20) and lean (n - 20) carcasses were selected, and their right and left sides were allotted alternately to either a non-spray chill cycle or to an intermittent cold water spray-chilling cycle lasting either 3 or 6 h. After 20 h of chilling, carcasses subjected to the 6-h spray had 12.9% more (P < .01) AT moisture and possessed 2.6% more moisture in the cutaneous trunci muscle than similar samples from the non-spray chilled counterparts. In comparison, AT samples that were subjected to the 3-h spray had 3.9% more (P < .65) moisture, and the cutaneous trunci muscle had 2.0% more moisture, than their dry-chilled counterparts. After chilling, the spray-chilled AT had substantially higher (P < .01) moisture in the fifth-rib region (26.1%) than in the sirloin (14.8%). Spray-chilled sides in the 6-h cycle gained .3% of their hot carcass weight, whereas the corresponding non-spray sides shrank 1.2%. Spray-chilled sides subjected to the 3-h cycle shrank .4%, and their dry counterparts shrank 1.1%. Carcass washing and length of spray cycle had a greater influence than carcass fatness on surface tissue moisture retention. Modulation of these factors will help control post-chilling fluctuation of carcass weights in excess of USDA regulations and yet maximize carcass weight yields.
Keywords: Food science; Beef; Adipose tissues; Carcass weight; Chilling; Shrinkage